Tingkat Kebersihan Peralatan Penjamah dengan Cemaran Bakteri Eschericia Coli dan Coliform pada Depot Air Minum Isi Ulang di Kelurahan Air Putih - Putri, Mirna Aulia; Kurniawan, Deny; Praminingsih, Vita (IAI Nasional Laa Roiba Bogor, 2025)
Water is an essential ingredient in human life, as every living creature desperately needs water. Businesses that typically manage drinking water are Refill Drinking Water Depots (DAMIU) to meet human needs in both unpackaged and bulk forms. One type of bacteria found in the intestine is Escherichia coli (E. coli). Some of these bacteria are pathogenic and can cause disease in humans. The purpose of this paper is to identify the cleanliness of drinking water depot facilities in the Air Putih sub-district and to identify E. coli and coliform content in these facilities. This study used descriptive research with an observational approach. Based on the results of the observation sheet previously described, a total of 14 DAMIUs were studied. The relationship between the presence of coliform and the presence of coliform bacteria was found in 14 DAMIUs. This finding is supported by a study. Other research also indicates that 63.3% of handlers do not meet the requirements. The conclusion of this study is that the cleanliness of drinking water depot facilities in the Air Putih sub-district area is descriptively good. However, 5 of the 14 DAMIUs contained coliform bacteria, while the other 9 were free of coliform.